A Novel Method for Determining Infiltration of Mechanically Ventilated Buildings. (7th February 2020) - Kulmala, Ilpo; Parviainen, Heikki; Hall, Ian; Pasanen, Pertti
Abstract : A novel method for determining air infiltration for mechanically ventilated buildings is presented in this paper. It consists of a model that uses size-resolved particle concentrations of the outdoor, filtered supply, and exhaust air as input. Based on these continuously measured concentrations, the infiltration rate can be inferred by fitting the experimentally obtained indoor concentrations with theoretically calculated values. The approach was validated by continuous long-term field measurements made over a four-month period. The results show that infiltration rates could be reliably estimated using this method and that the calculated infiltration rates were clearly dependent on the wind speed.